Factors Associated With Preference of Psychological Intervention and Mental Status Among Chinese Teachers During Coronavirus Disease 2019: A Large Cross-Sectional Survey - Lizhi, Xu; Peng, Cheng; Wanhong, Zheng; Shengmei, Xu; Lingjiang, Li; Li, Zhang; Xiaoping, Wang; Weihui, Li (Frontiers in Psychiatry, 2021)
Aims: The authors sought to explore the psychological distress of teachers during COVID-19 pandemic and their preference for psychological intervention. The overarching goal was to gain insight on how to build an effective psychological support system for teachers during and after the pandemic. Methods: The mental health condition of teachers (N=18,521) was assessed online by using a questionnaire consisting of standard instruments PHQ-15, GAD-7, PHQ-2, PC-PTSD, and additional questions about sleep disturbance, suicidality and preference of psychological intervention methods. Results: 35.5% of Chinese teachers reported sleep disturbance, 25.3% complained of somatic discomfort, 17.7% had anxiety symptoms, 4.0% had depression, 2.8% had self-injury or suicidal thoughts. Women are more likely to have somatic symptoms, sleep disturbance and depression. There were age differences for anxiety, somatic symptoms and suicidal thoughts. High percentages of university teachers reported moderate to severe anxiety, somatic symptoms, depression and sleep disturbance. The most preferred psychological intervention is the self-practice of stress management skills (N=11,477, 62.0%). Teachers with moderate and severe symptoms are more likely in need of hotline and online counselling and those with serious suicidal thoughts are three times more likely to use a telephone hotline. Conclusions: During the COVID-19 outbreak, the major reported psychological distress among Chinese teachers are anxiety, sleep disturbance and somatic symptoms. There were gender, age and school setting differences. Females, teachers over 45 years old and those who work at universities tend to be more vulnerable. Different teachers chose different interventions, mostly based on the severity of their symptoms.